2017
DOI: 10.1155/2017/9639306
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Analysis of the Effect of Dip-Spin Coating Process Parameters on Coating Thickness Using Factorial Design Method

Abstract: Statistical modeling of the dip-spin coating process to describe colloidal PTFE dispersion coating on the external surface of a small diameter hollow tube was developed by using 2 4 factorial design with a center point to predict the coating thickness in a range of 4-10 m. The coating parameters included viscosity, withdrawal rate, spin speed, and immersion time. The adequacy of the predicted model was verified by coefficients of determination and lack-of-fit test. Model accuracy was verified by comparing pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…A wet film with higher concentration was formed at the drying front, due to the higher ratio of surface area to volume, which results in the drawing of solution from surrounding area. When a dry film was formed at the drying front, a capillary force appeared on the solution, resulting in the thickening of the coated film [ 46 , 47 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…A wet film with higher concentration was formed at the drying front, due to the higher ratio of surface area to volume, which results in the drawing of solution from surrounding area. When a dry film was formed at the drying front, a capillary force appeared on the solution, resulting in the thickening of the coated film [ 46 , 47 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…The longer the immersion time of the 316L stainless steel substrate in the slurry, the thicker the resulting HA layer is. The thickness of the layer increases with an increasing immersion time [16]. The longer the immersion time, the longer the contact that occurs between the 316L stainless steel substrate with the HA slurry, so that the resulting layer is thicker.…”
Section: Sem Analysismentioning
confidence: 99%
“…The coefficients are quantitative measures of the effect of the parameters. The higher the coefficient value, the greater the effect of these parameters on the thickness of the HA layer [16]. Effect of the sintering temperature on the hydroxyapatite coating thickness.…”
Section: Empirical Model Of the Ha Coating Thicknessmentioning
confidence: 99%
“…The tensile strength and elongation at break were calculated with an average of five-sample values. The thickness was adjusted with a micrometer caliper [40].…”
Section: Mechanical Performancementioning
confidence: 99%
“…It has been observed that PLA/MMT nanocomposites can show significant improvement in mechanical properties of the material with the addition of MMT [39]. Pluta et al studied the structure, dielectric, viscoelastic, and thermal properties of PLA/MMT nanocomposites by using a melt blending technique [40]. In our previous study, we fabricated and characterized electrospun films from polylactic acid and CTAC-MMT clay [41].…”
Section: Introductionmentioning
confidence: 99%